1986
DOI: 10.1002/cyto.990070209
|View full text |Cite
|
Sign up to set email alerts
|

Physical discrimination between human T‐lymphocyte subpopulations by means of light scattering, revealing two populations of T8‐positive cells

Abstract: Light‐scattering properties of human T‐lymphocyte subpopulations selected by immunofluorescence were studied. Based on differences in orthogonal light scattering, two subpopulations of T8‐positive cells can be distinguished. The first population (T8a) has the same orthogonal light‐scattering properties as T4‐positive cells, whereas the orthogonal light scattering of the second population (T8b) was about 70% larger. Orthogonal light scattering of Leu7‐positive lymphocytes resembles that of the T8b population. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…It was demonstrated that these subpopulations consist of regulatory and Blymphocytes (low orthogonal light scattering signal) and cytotoxic lymphocytes (high orthogonal light scattering signal). In another report we have shown that the CD8 + lymphocyte population could be divided in a suppressor-and a cytotoxic lymphocyte CD8 + subpopulation [17].…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…It was demonstrated that these subpopulations consist of regulatory and Blymphocytes (low orthogonal light scattering signal) and cytotoxic lymphocytes (high orthogonal light scattering signal). In another report we have shown that the CD8 + lymphocyte population could be divided in a suppressor-and a cytotoxic lymphocyte CD8 + subpopulation [17].…”
Section: Introductionmentioning
confidence: 85%
“…A large variation in the occurrence of CD8 + subpopulations of healthy donors is observed [17]. CD8b+/CD8 + ratios varied from 17 to 69 (mean 39).…”
Section: Cd8a and Cd8b Determinationmentioning
confidence: 99%
See 3 more Smart Citations